Modelling Tariffs in TINFORGE – a Methodology Report - Anke Mönnig; Marc Ingo Wolter (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2020)
Studies on foreign trade and its economic impact are numerous. Ricardo's thesis that the international division of labour is welfare-enhancing, even if a country has comparative disadvantages in the production of all goods, became a basic assumption of economic thought. On this basis, free trade was considered superior to protectionism, although later studies such as Samuelson and Autor relativized Ricardo by showing constellations in which international division of labour can also lead to a permanent loss of welfare. For Germany, foreign trade has developed into one of the most important drivers of economic growth. Since the European Monetary Union, Germany's share of the balance of payments in gross domestic product has risen significantly and exceeded the six-percent mark for the first time in 2007. More than ever, foreign markets determine the success and failure of those sectors that have become – directly and indirectly – dependent on foreign demand. However, world trade not only affects the production structure of domestic industry, but also affects demand for employment. The number of people in jobs that are directly or indirectly linked to export flows continues to rise. Looking beyond the labour market, this also results in changes in occupations and qualification requirements. Particularly in the first decade of the post-war period, the sharp increase in world trade and thus its increasing importance can be explained by a reduction in trade barriers (within the framework of GATT/WTO, but also by increasing regional integration, e.g. by the EU or the North American Free Trade Agreement NAFTA2). Regional integration into the EU, but also the number of free trade agreements, has continued to increase. Further free trade agreements (e.g. between the EU and Canada and the EU and Japan) were also negotiated or concluded in 2017/2018. The worldwide average tariff rate declined to 2.6% (World Development Indicator, value for 2017). The World Trade Organisation (WTO) sets nowadays the framework of international trade. It currently holds 164 members that all agreed to the rules of the General Agreement on Tariffs and Trade (GATT). The aim of this trade agreement is to reduce tariffs and other trade barriers and to implement a non-discriminatory trade system that grants both the rights and obligations of its member countries. Non-discrimination of WTO members is guaranteed by the principle of the most favoured nation (MFN), in addition to the requirement to treat imported and domestic goods equally on the market. In addition to coordinating world trade, the WTO has a dispute settlement function. However, the possibilities for sanctions in the event of misconduct by members are limited. This can be observed by the present tariff war between USA and China, two members of the WTO. This goes in line with an observable strong current against globalisation and free trade. The failure of the TTIP negotiations, the US import tariffs on steel and aluminium, the escalating trade war between the USA and China and the "abuse of power" of tariffs in political disputes (USA and Turkey) show that free trade in goods and services is under pressure. Even within the European Union, the exit of Great Britain from the EU enhances the likelihood of reintroducing tariffs on European ground. For an economy like Germany which is strong in exports and which holds close economic linkages within the European Union and beyond, it is crucial to know the effects of free trade on the German economy. In order to be able to map such developments and assess the impact of trade barriers on the domestic labour market, the model TINFORGE has been further developed in such a way that trade barriers in form of tariffs are implemented product-specific and country-specific. The remainder of the paper is structured as follows: first a brief introduction to trade costs, the measurement of trade costs, the impact of tariffs on the economy as well as the reason for trade are given. Then, the modelling of tariffs in TINFORGE is described in greater detail. The methodology is then tested on a scenario of an increase in US import tariffs on EU motor vehicles. The paper closes with a summary and conclusion.
Keywords: F12; F17; F62; 330; Welthandelsmodell; Zölle; Methoden